One step forward, two steps back?: paradoxes of natural resources management decentralisation in Cameroon - Oyono, P.R. (2004)
Theory informs us that decentralisation, a process through which powers, responsibilities and resources are devolved by the central state to lower territorial entities and regionally/locally elected bodies, increases efficiency, participation, equity, and environmental sustainability. Many types and forms of decentralisation have been implemented in Africa since the colonial period, with varying degrees of success. This paper explores the process of forest management decentralisation conducted in Cameroon since the mid-1990s, highlighting its foundations and characterising its initial assets. Through the transfer of powers to peripheral actors for the management of forestry fees, Council Forests and Community [or Village] Forests, this policy innovation could be empowering and productive. However, careful observation and analysis of relationships between the central state and regional/local-level decentralised bodies, on the one hand, and of the circulation of powers, on the other, show – after a decade of implementation – that the experiment is increasingly governed by strong tendencies towards ‘re-centralisation’, dictated by the practices of bureaucrats and state representatives. The paper also confirms recent empirical studies of ‘the capture of decentralised actors’. It finally shows how bureaucrats and state authorities are haunted by the Frankenstein's monster syndrome, concerning state–local relationships in decentralised forest management.